EIB at a glance - European Investment Bank (European Investment Bank, 2024)
As the largest and greenest multilateral lender in the world, the EIB helps economies flourish, creates jobs and promotes equality. Since 1958, the EIB has provided loans and expert advice for thousands of projects in over 160 countries.